2014
DOI: 10.25103/jestr.073.07
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Performance of Chosen Models for the Estimation of Global Solar Radiation on Horizontal Surface - A Case Study in Terny Hdiel , Tlemcen of Algeria

Abstract: Any study or application of solar energy in a given site requires a complete and detailed knowledge of the available solar resources. Hence, the aim of this work is to evaluate global solar radiation on a horizontal surface in Teny Benu-Hdiel, Tlemcen, Algeria (latitude 34° 46'60" N, longitude 1°22'0" E) using measured meteorological data. The data were recorded in the period 1983 to 2005 using NASA's surface meteorology and solar energy-model. From these models, the new empirical constants have been obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
(2 reference statements)
0
4
0
Order By: Relevance
“…In addition, some hormones such as insulin promote the fat accumulation. Others like glucagon or adrenaline are lipolytic [ 31 ]. The ginger rhizomes essential oil because of these molecules possessing hypolipidaemic properties would increase the activity of lipolytic enzymes or hormones at the expense of enzymes and hormones that favor lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some hormones such as insulin promote the fat accumulation. Others like glucagon or adrenaline are lipolytic [ 31 ]. The ginger rhizomes essential oil because of these molecules possessing hypolipidaemic properties would increase the activity of lipolytic enzymes or hormones at the expense of enzymes and hormones that favor lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our research, we found that there are few cases reported in the scientific literature. In fact, in the scientific literature, there are very few cases of smart farms reported that can be compared with the data obtained in our case study, which will be referred as System A. Soufi et al [22] describes the sizing of a solar panel and its energy storage system (battery) for a stand-alone photovoltaic system (PVS) capable of supplying the necessary electricity to a rural farm in Algeria, hereinafter referred to as System B. Salihu et al [23] presented a photovoltaic system disconnected from the national distribution network for the rural electrification of a farm in Nigeria, which will henceforth be referred as System C. The work carried out centered on the construction and implementation of a small photovoltaic network. On the other hand, Ibrik [24] focused his work on aspects related to the impact of using solar photovoltaic systems in a rural microgrid located in Palestine, which will henceforth be referred as System D. Table 2 shows some of the most important characteristics of the solutions studied and proposed in the aforementioned works, comparing them with the characteristics of the research case proposed in this study.…”
Section: Comparison With Similar Casesmentioning
confidence: 63%
“…Over the last decades, there were considerable endeavors for evaluating and interpreting the Angstrom-Prescott equation [60]. New formulations (either linear or non-linear) of the Angstrom-Prescott equation were proposed by many researchers using clearness index against sunshine fraction [8,36,47,57,[61][62][63][64][65][66][67][68][69], ambient temperature [8,47,62,67,69,70], relative humidity [8,47,69], precipitation [47,62,71,72], cloud cover [47,57,61,73], and multi-parameters [47,60,67,69,74].…”
Section: Existing Models and Methodsmentioning
confidence: 99%